The Texts Flow Structure of students' English speech Performance in the Seminar Course on ELT (Anthropolinguiistics approach) - Octavianna, Yessy; Carolina Pakpahan (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
The purpose of this paper is to describe (1) what are the text flow structures of the of students' English speech performance and (2) what is the non-text flow structure of the students' English speech performance in the Seminar on ELT course. Methods: This study was observed using an anthropolinguistic approach using analytical parameters, namely interconnection, valuability, and sustainability. A qualitative paradigm with an ethnographic model is used in this study by applying twelve steps both in interview and observation methods. Findings: The text flow structure of the of students' English speech performance has three important patterns, namely the introduction, body, and conclusion. It has the smallest elements called substructure. The substructure, there are greeting, question, and declarative sentences found in introduction. The substructure, there are transitional speech, guess, question, declarative, and explanatory sentences found in closing, and greeting closing found in closing part. In the non-text flow structure of the students' English speech performance found co-text and context elements, they are cultural, social, situational, and ideological contexts. In co-text found kinesics and prosemics. Conclusions: The text flow structure is the basic framework of a text in forming a coherent whole. The text and non-text flow structure is related to the text framework which is arranged regularly from beginning to end starting with the introduction into the conclusion. Both the text and non-text flow structures are very necessary to improve students’ ability to communicate well and creatively.